Pendugaan Tingkatan Bahaya Erosi pada Tanaman Kopi (Coffea Sp.) di Beberapa Kecamatan di Kabupaten Dairi - Ledi Kiswanto Barus; Hardy Guchi; Posma Marbun (Universitas Sumatera Utara, 2015)
This study aims to determine the level of danger of erosion on land coffee plant ( Coffea Sp ) insome of the District Dairi . Coffee plants can grow in a variety of soil types and grows well ataltitude 800 sd 2000 m above sea level , the temperature is 15 sd 25oC , rainfall 1,750 mm peryear sd 3.000 and pH 5.5 up to 6.5 . Number of Production Smallholders 2758.85 tonnes ofRobusta and Arabica coffee 10088.50 tonnes . In 2006 amounted to 2,865 tons , an increase of18,168 tonnes (2008 ) , dropped to 2,060 tons (2009 ) , be 12 847 tonnes (2010 ). 19,000 hectaresof land used , used for Robusta coffee smallholders and 8,495 for Arabica coffee 10504.5hectaresKeyword : Coffee Plant, Soil Slope, Erosion potential.